Integrative taxonomy of the cave-dwelling mysids of the genus Hemimysis. Issue 3 (3rd April 2019) - Lunina, Anastasia A.; Nikitin, Mikhail A.; Shiian, Aleksandra S.; Ereskovsky, Alexander V.; Kovtun, Oleg A.; Vereshchaka, Alexander L.; Ivanenko, Viatcheslav N.
Abstract : The genus Hemimysis (Malacostraca: Mysida: Mysidae) encompasses near-bottom, demersal and cave-dwelling mysids living in the marine, brackish and freshwater habitats around the European coast, from the Caspian Sea to the Scandinavian Peninsula. We conducted cladistic analysis of 52 morphological characters of all nine species and three subspecies of the genus Hemimysis. We also completed a molecular analysis based on three molecular markers of Hemimysis lamornae (Couch, 1856) found in the English Channel, the Mediterranean Sea, and the Black Sea. Both analyses did not support monophyly of Hemimysis lamornae . We thus consider the former subspecies H. lamornae pontica (Czerniavsky, 1882 ) and H. lamornae mediterranea Bacescu, 1936 as valid species. Analysis of mitochondrial cytochrome oxidase subunit I (COI) sequences of H. pontica shows no significant divergence between mysids living in the marine caves of Crimea and Bulgaria. Morphological trends in Hemimysis are discussed, H. pontica Czerniavsky, 1882 is redescribed, and a new key to all 11 species of the genus is given.